(untitled) (Jurnal Ilmiah Psikologi MIND SET, 2023)
The Covid-19 pandemic has brought about significant changes in the field of education, with traditional face-to-face learning transitioning to online instruction, resulting in a one-directional and monotonous learning experience that can lead to feelings of boredom. Boredom, which is an unsatisfactory state, can be counteracted by the positive individual characteristic of mindfulness. This study aims to explore the relationship between mindfulness and boredom in students who are attending online classes. A correlational quantitative approach was used in this study, employing a convenience sampling technique that resulted in a sample size of 346 students, consisting of 73 males and 273 females. Individual mindfulness was measured using the Mindful Attention Awareness Scale (MAAS) (α = 0.859), while boredom was measured using the Multidimensional State Boredom Scale (MSBS) (α = 0.953). The study revealed that there was a significant negative correlation between mindfulness and boredom (r = -0.295; p = 0.001). Furthermore, mindfulness was found to be significantly negatively correlated with four of the five dimensions of boredom, namely disengagement, high arousal, inattention, and low arousal (r = -0.239, r = -0.339, r = -0.321, r = -0.280). These findings suggest that individuals who exhibit higher levels of mindfulness are less likely to experience boredom. Therefore, the study concludes that mindfulness can help individuals regulate their attention and emotions, thereby mitigating the harmful effects of boredom.